Kingdom of Netherlands : Netherlands; Selected Issues and Analytical Notes. (IMF Staff Country Reports; Country Report ;, 2011)
Important issues of the Netherlands are discussed. Openness to trade has benefited the Netherlands before the crisis and has supported the recent recovery process. However, both financial openness and trade linkages have also been a transmission channel for the financial crisis. Synchronized fiscal tightening across Europe has important spillover effects for GDP growth. The improvement on the supply side of credit has contributed to a normalization of the credit market. However, the recent increase in the financial stress index indicates that the situation is still fragile.